'Little New Meat' and 'Korean Warm Men': Performance of regional heterosexual masculinities among Taiwanese millennials. Issue 1 (1st April 2020) - Shiau, Hong-Chi
Much of the academic research on the Korean Wave has focused on transcultural hybridity, with little analysis of how the Korean Wave has challenged and reshaped the site of heterosexual masculinities among millennials. Through ethnographic and focus-group interviews, this article explicates how Taiwanese masculinities have been negotiated and constructed in response to the Korean Wave, based on both Taiwan and Korea sharing a Confucian culture that emphasizes diligence and responsibility, and the popularity of refined and sophisticated men as male role models. These localized influences have compromised the 'hegemonic masculinity' in the West. Various contradictory attributes of Taiwanese masculinity interact with one another, but this article elicits three themes: soft/'wen' masculinity, a sculptured by not excessively muscular body and male-bonding. The results illustrate how the boundaries between hegemonic and marginalized forms of masculinities in Taiwan, similar to in the West, are often more interactive than oppositional. While there are contradictory attributes respond to one another, this article illuminates how a dominant form of Taiwanese masculinities prevails among the Taiwanese male millennials. Ultimately, consumerism has significantly influenced the construction of masculinity and led to diversity in masculine discourse.